PENDEKATAN SPIRITUAL DALAM KONSELING PENGEMBANGAN HIKMAH IBADAH BAGI PEMULIHAN PECANDU NAPZA - Cucu Maesaroh (Sosio Konsepsia, 2009)
This research is aimed at finding a formula of spiritual approach in the counseling of the development of the worship blessing for the rehabilitation of drugs addict provided by Balai Pemulihan Sosial Pamardi Putra Lembang (Drugs Addicts Social Rehabilitation Organization). It applied the qualitative method by using collaborative action research approach. The gained results are : (1) the change in physical, social, and mental-spiritual structures; (2) the change in personalitiJ with noble character which can give advantages to the addicts themselves, family environment, and social environment around them; (3) the development of mature personality which is balanced psychological or emotionally, socially, and mentally-spiritually ofdrugs addicts which can become an internal factor of personal strength and unihJ to reach the true happiness; and (4) can reach divine potential, so, the addicts can solve their life problems wisely, including the problems of relapses, with this potential.